Expert opinion on clinical experience with subcutaneous interferon beta‐1a in multiple sclerosis patients with different disease activity profiles. Issue 5 (26th June 2019) - Bohlega, Saeed; Alroughani, Raed; Alkhawajah, Mona; Alsaadi, Taoufik; Daif, Abdulkader; Elalamy, Osama R.; Inshasi, Jihad S.; Noori, Suzan; Shakra, Mustafa; Shatila, Ahmed O.; Boghdady, Ahmed El; Boshra, Amir
Abstract: Latest diagnostic criteria have increased the speed and accuracy of multiple sclerosis diagnosis. Early diagnosis of multiple sclerosis and early treatment initiation help in achieving better clinical outcomes. Accordingly, recent clinical studies include patients with less severe multiple sclerosis as compared to older studies, and in this milder multiple sclerosis population, many patients do not progress over 2 years. Interferon beta‐1a has been used for the treatment of relapsing multiple sclerosis for more than 20 years and has been assessed in multiple clinical trials of varying lengths. Clinical trials of subcutaneous interferon beta‐1a show efficacy in terms of relapse rate, magnetic resonance imaging outcomes, and long‐term disability measures in relapsing multiple sclerosis patients with different disease activity profiles. This article discusses multiple sclerosis experts' opinions on the level of disease activity of the patient populations used in the clinical trials of subcutaneous interferon beta‐1a and on the effectiveness of subcutaneous interferon beta‐1a in these patient populations. Based on experts' opinions, it can be concluded that patients with mild or moderate disease activity have a high potential of benefiting from high‐dose subcutaneous interferon beta‐1a.